Neuroendocrine carcinoma of the uterine cervix: 15-year experience from a tertiary care centre in Southern India. Issue 2 (27th June 2021) - Jacob, Sobin V.; Sathyamurthy, Arvind; Ramireddy, Jeba Karunya; Thomas, Anitha; Singh, Kaalindi; Ram, Thomas Samuel
Abstract: Aim: To analyse the presentation, treatment strategies and outcomes of neuroendocrine carcinoma of cervix treated with multi-modality approach at our institute. Materials and methods: The data of patients diagnosed to have cervical cancer between October 2004 and November 2018 were retrieved, and 14 patients of neuroendocrine carcinoma cervix who received treatment in our institution were identified. The patients were analysed based on demographic characteristics, disease stage, pathological characteristics, treatment and follow-up. The median overall survival and disease-free survival were calculated. Results: Median follow-up period was 8 months (range 1–52 months). Six patients died within 4 months of completion of treatment due to disease progression. Median overall survival was 12 months and median disease-free interval was 5·5 months. Four of the patients who underwent combined modality treatment consisting of neoadjuvant chemotherapy, concurrent chemoradiation therapy and brachytherapy are still on regular follow-up and are disease-free. Conclusion: Neuroendocrine carcinoma of the cervix is a rare but aggressive histological subtype. Combined modality approach with judicious use of systemic chemotherapy along with surgery and radiation therapy is essential for optimal outcomes.